Transanal endoscopic microsurgery in treatment of rectal adenomas and T1 low-risk carcinomas - Amann Michael (World Journal of Surgical Oncology, 2012)
Abstract Background Transanal endoscopic microsurgery as a local therapy option for rectal neoplasms is a tissue-sparing technique that protects the anal sphincter. The present retrospective analysis reports the course of observation after local excision of adenomas and T1 low-risk carcinomas using transanal endoscopic microsurgery. Methods In a retrospective analysis we examined data on 279 patients for local recurrence. A total of 144 patients had a rectal adenoma (n = 103) or a R0 resection of low-risk T1 carcinomas (n = 41). In this collective, we also examined parameters concerning perioperative management, complications, intraoperative blood loss and duration of hospital stay. Results Patients with adenoma were on average 64.9 (range 37 to 90) years old; 83.5% of the adenomas were located 3 to 11 cm from the anocutaneous line. In adenoma patients the recurrence rate was 2.9% for an observation period of 21.8 months. The postoperative course was without any complications in 98.1% of patients. Patients with T1 low-risk carcinoma were 64.6 (range 30 to 89) years old. In all cases, an R0 resection could be performed. The recurrence rate was 9.8% for an observation period of 34.4 months. In this group the postoperative course was free of complications in 97.6% of patients. Conclusions The high efficacy of transanal endoscopic microsurgery ensures minimally invasive treatment of adenomas and low-risk T1 carcinomas with low complication rates and a low rate of therapeutic failure.